A Longitudinal Analysis of Cognitive Transitions: A Case Study on the Evolution of Pre-operational to Concrete Operational Mindsets in Children Aged 5–7 - Novi Ayu Kristiana Dewi (Journal of Transdisiplinary Studies in Education, 2026)
Background: The transition from pre-operational to concrete operational thinking is a fundamental stage in children's cognitive development. Despite its importance, classroom practices often prioritize early mastery of literacy and numeracy through memorization, with limited attention to children's developmental readiness. As a result, learning difficulties at an early age are frequently interpreted as indicators of limited ability rather than as part of a normal cognitive transition. Aims: This study explores how a child's cognitive processes changed between the ages of five and seven, with particular attention to the development of logical reasoning during the transition from the pre-operational to the concrete operational stage. Methods: A qualitative longitudinal single-case study was conducted over a two-year period involving one purposively selected child. Data were gathered through participatory observations, Piagetian clinical interviews, and an analysis of learning portfolios. The data were examined using a constant comparative approach, and evidence from multiple sources was triangulated to strengthen the trustworthiness of the findings. Results: The child gradually shifted from intuitive, perception-based responses to more systematic and logical reasoning. Initial dependence on concrete representations in arithmetic was replaced by conceptual understanding, accompanied by stronger metacognitive awareness, independent reasoning, and more reflective approaches to problem solving. Conclusion: The findings indicate that early academic difficulties should be interpreted within the context of cognitive development rather than as evidence of low intellectual ability. Recognizing individual developmental trajectories can help educators design learning experiences that encourage reasoning, inquiry, and conceptual understanding instead of emphasizing memorization alone.